Math Questions and Answers

Start Your Free Trial

Prove the identity: (cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)

Expert Answers info

Tushar Chandra eNotes educator | Certified Educator

calendarEducator since 2010

write12,554 answers

starTop subjects are Math, Science, and Business

 

The identity `(cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)` has to be proved.

Start from the left hand side.

`(cos x + cos y)^2 + (sin x – sin y)^2`

=> `cos^2...

(The entire section contains 110 words.)

Unlock This Answer Now


check Approved by eNotes Editorial


oldnick | Student

`(cosx+cosy)^2+(sinx-siny)^2=(2cos((x+y)/2)cos((x-y)/2))^2+(2sin((x-y)/2)cos((x+y)/2))^2=`

`=4cos^2((x+y)/2)cos^2((x-y)/2)+4sin^2((x-y)/2)cos^2((x+y)/2)=`

`=4cos^2((x+y)/2)(cos^2((x-y)/2)+sin^2((x-y)/2))=`

`=4cos^2((x+y)/2)` `=2(1+cos(x+y))=2+2cos(x+y)`